The development of local government in Ireland - Horgan, John J. (Statistical and Social Inquiry Society of Ireland, 1946)
Although I am only a new recruit to the ranks of this Society I have noticed that your proceedings are, as a rule, more concerned with the first rather than the second object of your title. I propose this evening to make some attempt to redress the balance in a paper which deals with an important social problem without reference to statistics. It may, I think, be said without exaggeration that national government is, in the last analysis, based on a sound system of local government. In this field we in Ireland have, since the establishment of the Irish State, made several fruitful experiments, and further developments may be expected as we mature politically. I propose in this paper to discuss the scope and effect of these changes and their future development.
Read on Thursday, 1st March, 1945
Keywords: Irish local government; Local government history; Local government development; 314.15